2012
DOI: 10.1590/s0103-90162012000200002
|View full text |Cite
|
Sign up to set email alerts
|

New mechanized system for circle spraying of oil palms seedling emergence

Abstract: ABSTRACT:, A new machine system has been designed, developed and evaluated for extensive circle spraying of oil palms (Elaeis guineensis Jacq.) in an effort to overcome the inefficient spraying problem with the conventional spraying system. The machine system consists of a four-wheeled drive 4WD prime mover with front mounted machine attachments for the circle spraying operation.The configuration of the circle spraying attachment consists of a hexagonal curved spray boom, lifting arm, opening-tilting mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The proposed estimated economic life was considered since the prime mover itself acts as a universal carrier for conducting other field operations such as field seedling transplanting, circle spraying, and in-field FFB collection-transportation. The total annual operating hours for the individual machine systems were estimated based on the listed parameters (Pebrian and Yahya, 2012;Roodi et al, 2011) as shown in Table 6.…”
Section: Costs Analysismentioning
confidence: 99%
“…The proposed estimated economic life was considered since the prime mover itself acts as a universal carrier for conducting other field operations such as field seedling transplanting, circle spraying, and in-field FFB collection-transportation. The total annual operating hours for the individual machine systems were estimated based on the listed parameters (Pebrian and Yahya, 2012;Roodi et al, 2011) as shown in Table 6.…”
Section: Costs Analysismentioning
confidence: 99%